Stereocontrolled Pericyclic and Radical Cycloaddition Reactions of Readily Accessible Chiral Alkenyl Diazaborolidines. Issue 30 (8th June 2022) - Zhang, Mingkai; Xu, Peilin; Vendola, Alex J.; Allais, Christophe; Dechert Schmitt, Anne‐Marie; Singer, Robert A.; Morken, James P.
Abstract: In this paper is described an easily synthesized chiral diazaborolidine that is inexpensive, stable, and provides excellent stereoselection across a number of reaction classes. These versatile compounds possess utility in four different classes of cycloaddition reactions, offering good yield and stereoselectivity. X‐ray structure analysis provides insight about the origin of stereocontrol. Abstract : Chiral diazaborolidines that are easily prepared, inexpensive, stable, and provide excellent stereoselection across a number of reaction classes are described. These versatile compounds can be used in four different classes of cycloaddition reactions, offering good yield and stereoselectivity.